GAMBARAN STATUS GIZI MAHASISISWA PROGRAM STUDI SARJANA GIZI SEKOLAH TINGGI ILMU KESEHATAN SAMARINDA - Prihandani, Erlingga; Sa’apang, Ferliani Fransisca; Tuerah, Patrisia Maria Estefania; Salsabila, Nasywa Nida (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Good nutritional status is crucial for students as it can significantly affect their energy levels, concentration, and productivity in daily activities. The importance of nutritional status necessitates that students strive to achieve a balanced diet. The food consumed plays a vital role in determining an individual's nutritional status. Both undernutrition and overnutrition can lead to various health issues. The objective of this study is to determine the nutritional status profile of undergraduate students in the Nutrition Study Program at the Samarinda Health Sciences College. The research method employed is descriptive research with total sampling. The population of this study consists of all students in the Nutrition Study Program at the Samarinda Health Sciences College, totaling 32 individuals. The findings of this study reveal that the majority of students have a normal nutritional status, accounting for 50%, followed by students with an obese status at 34.3%, then students with an overweight status at 9.3%, and students with an underweight status at 6.2%. The nutritional status of students is influenced by various factors such as lifestyle related to unhealthy eating patterns.